Load-Bearing Capacity of Klein’s Ceiling Under Fire Conditions - Katarzyna Rzeszut; Bartosz Gościński (Buildings)
The aim of this study was to determine the load-bearing capacity of Klein’s floors under fire conditions using analytical and numerical analyses. Analytical and numerical simulations were performed considering different structural variants of Klein’s floors. A numerical FEM model was developed in Abaqus to create temperature profiles of the beam-to-beam slabs and steel beams, and the fire load-bearing capacity of Klein’s celling after being exposed to fire for 30, 60, and 120 min was calculated analytically. The analytical method of assessing the fire load-bearing capacity of Klein’s floors uses temperature profiles, which allow for calculations to verify fire resistance in the time domain of different structural variants of Klein’s floors. (1) Introduction: The structural solutions of Klein’s floors are widely known, but no studies in the literature have addressed the mechanics of these elements under fire conditions. Both the beam-to-beam slab and steel beams are sensitive to high temperatures. Providing the required level of fire safety in buildings with Klein’s ceilings is a complex issue that requires detailed analysis. This often involves the assessment of technical and material solutions that are not currently used, and a verification of their fire resistance may be necessary to adapt existing buildings to the presently applicable technical and construction regulations. (2) Methodology: This study was prepared based on domestic and foreign sources, including standards presenting available methods for verifying the fire resistance of Klein’s ceilings in terms of their load-bearing capacity. A calculation scheme was indicated that takes into account the inter-beam slab, treated as a reinforced masonry element subjected to bending, and steel ceiling beams. In addition, this article presents an original method for determining the temperature profiles of individual elements of Klein’s ceilings, based on numerical methods, to determine their reduced values of material properties. The temperature profiles included in this study take into account both different construction variants of Klein’s ceilings and different ways of finishing the lower surface of these ceilings. The presented analytical method of fire load-bearing capacity assessment is supported by a calculation example. (3) Conclusions: The calculation methodology presented in this paper, which is part of the analysis of the fire load-bearing capacity of Klein’s ceilings, allows for a safe estimation of their durability in fire conditions. The presented temperature profiles of individual Klein’s ceiling elements allow for the verification of their fire resistance in terms of load-bearing capacity, in accordance with the literature on the subject. The temperature values of individual Klein’s ceiling elements, presented in the form of a table, depending on the fire duration, indicate that the applied structural solutions of the ceilings have a significant influence on the rate of temperature increase in the partition. Based on the conducted analyses, it was found that steel beams in an unplastered Klein’s ceiling lose their fire load-bearing capacity before the 30 min fire duration, defined by the standard temperature–time curve. The use of gypsum plaster with a thickness of at least 1.5 cm can provide fire resistance of the above elements for up to 120 min of fire duration. It was found that the quality of the plaster is important, influencing its adhesion to the lower surface of the ceiling. The fire resistance of the inter-beam slabs is significantly influenced by the temperature of their reinforcement, which largely depends on the distance of the reinforcement from the lower edge of the slab.